Effects of progesterone vs. dexamethasone on brain oedema and inflammatory responses following experimental brain resection. (November 2014) - Xu, Fei-Fan; Sun, Stella; Ho, Amy S. W.; Lee, Derek; Kiang, Karrie M. Y.; Zhang, Xiao-Qin; Wang, Anna M.; Wu, Ed X.; Lui, Wai-Man; Liu, Bai-Yun; Leung, Gilberto K. K.
Abstract Background: Dexamethasone (DEXA) is commonly used to reduce brain swelling during neurosurgical procedures. DEXA, however, has many side-effects that can increase the risks of post-operative complications. In contrast, progesterone (PRO) has fewer side-effects and has been found to be neuroprotective on traumatic brain injury (TBI). Whether PRO may be used as an alternative to DEXA during routine procedures has not been fully explored. Object: To compare the effects of DEXA and PRO on surgical brain injury (SBI). Methods: Seventy-five adult male Sprague Dawley rats were randomized into five groups: (1) SBI + drug vehicle (peanut oil, 1 ml kg−1); (2) SBI + DEXA (1 mg kg−1); (3) SBI + low-dose PRO (10 mg kg−1); (4) SBI + high-dose PRO (20 mg kg−1); and (5) sham SBI + drug vehicle. Magnetic resonance imaging study and assessments of brain water content (BWC), blood–brain barrier (BBB) permeability, cellular inflammatory responses and matrix metalloproteinase 9 (MMP-9) expression were conducted. Results: This model consistently resulted in increased BWC and BBB disruption. PRO reduced astrocyte and microglia responses and attenuated brain oedema with preservation of BBB. A significant down-regulation of MMP-9 expression occurred in the PRO 20 group. Conclusions: PRO is as effective as DEXA in reducing brain oedema and inflammation following SBI; 10 mg kg−1 of PRO was demonstrated to be more effective in relieving acute cellular inflammatory responses.